1998
DOI: 10.1046/j.1365-2044.1998.00321.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of low‐dose mivacurium to facilitate insertion of the laryngeal mask airway

Abstract: SummaryWe have evaluated the effects of the volume and speed of administration of local anaesthetic during peribulbar anaesthesia. One hundred and forty patients scheduled for cataract surgery were randomly allocated to one of four groups of 35. Each patient received an injection of the same mixture of lignocaine, bupivacaine and hyaluronidase. Patients in group A were given 9 ml at a speed of 5 ml.min À1 , group B were given the same volume at 12 ml.min À1 , group C were given 13.5 ml at 5 ml.min À1 and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 13 publications
4
29
0
Order By: Relevance
“…They did not determine if mivacurium was effective for LMA insertion if thiopental had been used as the induction agent instead of propofol. 19 D'Honneur found that priming doses of atracurium (0.05 and 0.075 mg-kg -1) depressed swallowing. 2~ We suggest that the combination of low dose atracurium depressed the pharyngeal and laryngeal reflexes sufficiently to allow successful LMA insertion.…”
Section: Discussionmentioning
confidence: 99%
“…They did not determine if mivacurium was effective for LMA insertion if thiopental had been used as the induction agent instead of propofol. 19 D'Honneur found that priming doses of atracurium (0.05 and 0.075 mg-kg -1) depressed swallowing. 2~ We suggest that the combination of low dose atracurium depressed the pharyngeal and laryngeal reflexes sufficiently to allow successful LMA insertion.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to improve the insertion conditions without increasing the dose of propofol, short-acting opioids, muscle relaxants, or midazolam may be co-administered with propofol to facilitate LMA insertion. [4][5][6] Intravenous lidocaine is known to suppress cough reflexes and reduce cardiovascular responses associated with tracheal intubation. 7 Its use prior to induction has been reported to improve LMA insertion conditions, 8,9 but not to reduce propofol requirements.…”
Section: Résumémentioning
confidence: 99%
“…A three-point, six-category scale (a-f) that had been used in previous studies [6,9,10] was used to grade insertion conditions. The three grades were scored 1, 2 or 3 in order of severity.…”
Section: Data Collectionmentioning
confidence: 99%
“…If malpositioned it can obstruct the airway and inadequate depth of anaesthesia may result in the patient coughing, gagging and rejecting the cLMA [3]. To provide reliable insertion conditions, a number of induction agents and adjuncts have been investigated [4][5][6][7][8]. Propofol 2.5-3.5 mg.kg )1 appears to be the most appropriate induction agent [4,8], but the choice of adjunct is less clear.…”
mentioning
confidence: 99%